Innovative Capability and Financing Constraints for Innovation: More Money, More Innovation? - Hottenrott, Hanna; Peters, Bettina (The Review of Economics and Statistics, 2012)
This study presents a novel empirical approach to identify financing constraints for innovation based on the concept of an ideal test (Hall, 2008). Firms were offered a hypothetical payment and asked to choose between alternatives of use. If they selected additional innovation projects, they must have had some unexploited investment opportunities that were not profitable using more costly external finance. We attribute constraints for innovation not only to lacking financing, but also to firms' innovative capability. Econometric results show that financial constraints do not depend on the availability of internal funds per se but that they are driven by innovative capability.